Hubungan Kadar Glukosa Darah Saat Mulai Dirawat Dengan Defisit Neurologis Pasien Stroke Iskemik - Kristanti, Ellya Afiani; Dr. Iwan Setiawan, Dr. Iwan Setiawan Sp. S, M.Kes (2017)
Background: Stroke is the second highest cause of death and the leading cause of disability in the world. Based on data from the World Health Organization, 20.5 million people in the world have suffered a stroke in 2011 and 5.5 million people have died. One of the risk factors that cause stroke is an increase in blood glucose levels. hyperglycemia worsens the prognosis by means of intracellular acidosis because of an increase in lipolysis, impaired blood-brain barrier, spur hemorrhagic infarction conversion,accumulation of glutamate, and brain edema.Objective: The aim of this study was to determine the relationship of blood glucose levels when first admitted to hospital with neurological deficit in ischemic stroke patients.Methods: The research was using analytic observational design with cross sectional approach. The data obtained are presented in tabular form, then analyzed using Fisher test at significance level of p = 0.004.Results: : The count of ischemic stroke patients have blood glucose high-level for 21 people, with light-level neurological deficit are 2 people (22.2%), medium-level are 7 people (36.8 %), heavy-level are 12 people (85.7%) whereas the people that have normal level of blood glucose for 21 people with light-level neurological deficit are 7 people (77.8%), medium-level are 12 people (63.2%), heavy-level are 2 people 14.3%). The results of the analysis data is obtained p-value = 0.004Conclusion: The conclusion of this study is there was significant relationship between blood glucose levels when first admitted to hospital with neurological deficit in ischemic stroke patients.Keywords: blood glucose, ischemic stroke, neurological deficit